Healthcare Utilization and Costs Among US Adolescents With Alopecia Areata - Markqayne Ray; Elyse Swallow; Kavita Gandhi; Christopher Carley; Vanja Sikirica; Travis Wang; Nicolae Done; James Signorovitch; Arash Mostaghimi (Journal of Health Economics and Outcomes Research)
**Background:** Alopecia areata (AA) is an autoimmune disease of hair loss affecting people of all ages. Alopecia totalis (AT) and universalis (AU) involve scalp and total body hair loss, respectively. AA significantly affects quality of life, but evidence on the economic burden in adolescents is limited.